Influence mechanism of visual perception of edge rate lines cycle length on driver’s speed - Liu, Bing; Zhu, Shunying; Wang, Hong; Xia, Jing; Ding, Naikan (Transport, 2021)
It is known that the installation of edge rate lines can help reduce driving speed. Theoretically, higher edge rate density leads to higher perception speed, so as the effect of speed reduction. However, there has not been a successful evaluation of appropriate design cycle length requirements. A series of experiments were taken on the straight sections on Hangrui highway in China. The cycle length was separately set in different values of 16, 8, 4, 2 and 1 m. The results showed that cycle length had significantly influence on the speed reduction effect. When the length of spatial edge rate line in each cycle λ equalled to the value of 16, 8, 4, 2 m, the effect of speed reduction was significantly enhanced as λ decreased. Percent of average speed reduction was 0.8, 3.0, 5.8 and 7.4%, respectively. However, when λ = 1 m, speed reduction effect was weaker than λ = 2 m, reduction percent of average speed was 5.2%. Then, relations between acceleration and average edge rate was analysed. When temporal frequency of edge rate lines fell in (10 Hz, 19 Hz], the braking deceleration of drivers increased as the temporal frequency increased, which conformed to the relation between temporal frequency and perception speed; when temporal frequency was lower than 10 Hz, some drivers will speed up. It may be related to the threshold of perception speed difference; when temporal frequency was higher than 19 Hz, some drivers will speed up. It may be related to flicker fusion phenomenon. According to the experiments results, edge rate lines cycle length for future implementations should be determined by the speed distribution of the target road. First published online 19 August 2020